Strategi Pengembangan Usaha Sayur Organik pada CV Golden Leaf Farm Bali - TIN. Roosany; IG. Setiawan Adi Putra; NW. Sri Astiti (Universitas Udayana, 2014)
The increasing competition in the organic vegetable industry, requires companies to develop their business plan with the right strategy. This study aims to analyze the company's internal strategy in winning the market, from the aspects of production and finance. This research was conducted in the CV. GLF Bali, with a focus on production and financial management of the company. The data was analyzed by qualitative and quantitative descriptive method. The production aspect was analyzed by production cost, cost of sales, product margins. And then, the financial aspect was analized by the balance sheet, income statement, cash flow statement, and financial ratio. The result of analysis showed, CV. GLF Bali could determine the cost of goods sold and selling prices exactly. So that, price of its products in the market is higher than competitors. CV Bali GLF can determine the cost of production of each budget period to the optimal and results from linear trend analysis showed a positive pattern. The cost of production per unit product tends decreased followed by an increasing production capacity. CV GLF Bali has a strong competitiveness in the market from the aspects of price and quality of the product because it has a good brand image. Financial Management of CV. GLF Bali classified in sound or good condition which showed by the results of the company's financial ratio and cash flow analysis. CV. GLF Bali has a good financial performance. CV GLF Bali used differentiation or uniqueness of product value by POAC (planning, organizing, actuating, and controlling) approach strategy to win a sustainable competition. Based on the study results and conclusions can be suggested: To increase sales turnover, CV management. GLF Bali in order to increase the production volume of rucola Wild type plants that have pretty good prospects through cost efficiency of production, so that it can compete in the market to target the upper middle class, by designing the minimum cost per unit of production and maximize profits. With good financial position suggested that CV. GLF Bali maximize the utilization of existing land to produce more organic vegetables. Management CV. GLF Bali to apply QQE (quality, quantity, efficiency) to improve cost efficiency, especially labor costs each planting period.